Deep-ultraviolet detectors based on oxygen-/fluorine-terminated (100) diamond. (December 2016) - Li, F.N.; Zhang, J.W.; Wang, X.L.; Liu, Z.C.; Wang, W.; Fu, J.; Zhu, T.F.; Wang, H.X.
Abstract: In this study, deep-ultraviolet detectors based on oxygen-/fluorine-terminated (100) diamond (O-/F-diamond) have been fabricated. Both of the O-/F-diamond surfaces have been formed on different areas of one (100) diamond sample by O2 and CF4 plasma. Pd has been evaporated on the O-/F-diamond surfaces to form Schottky contact, whose barrier heights have been investigated by X-ray photoelectron spectroscopy technique. Deep-ultraviolet detector based on F-diamond shows lower dark current than that based on O-diamond. Highlights: Deep-ultraviolet detectors based on oxygen-/fluorine-terminated (100) diamond have been fabricated. The deep-ultraviolet detector based on F-diamond shows lower dark current than that based on O-diamond. The deep-ultraviolet detector based on F-diamond shows shorter response time than that based on O-diamond. The F-diamond is very stable, showing a little loss of fluorine after hot acid treatment. The Schottky barrier height for Pd/F-diamond is higher than that for Pd/O-diamond.